Generativni pristop k učinkovitemu načrtovanju objektov - Gradišar, Luka (Gradbeni vestnik, 2021)
When designing, we often face problems for which we must find a solution. We solve such problems iteratively by proposing a solution, analysing it and testing its suitability until the solution satisfies all conditions and objectives. Normally we solve such problems based on experience and knowledge, which does not work for the problems we are confronted with for the first time. An alternative approach is generative design, where we focus on defining a problem with its objectives and constraints in terms of a parametric computational model and leave the solution to the algorithms. The result of the generative process is a set of solutions the analysis of which helps us to solve the problem. The main idea of the approach is the collaboration between the designer and the intelligent tool, which has complementary capabilities, such as sorting large amounts of data, generating many alternatives, analysing the solutions, and incrementally improving them. The approach is general and can also be applied in other areas of civil engineering. In this paper, we question the capacity of such an approach and whether it aims to replace the designer in the design process. Therefore, in the first part we present the key elements of generative design, in the second part we apply the generative design process for the design of shading elements, and in the last part we present the results and compare them with the usual approach.
Keywords: BIM; computational model; Dynamo; evolucijski algoritmi; evolutionary algorithms; generative design; generativno načrtovanje; optimisation; optimizacija; računski model